Pengaruh Promosi, Kualitas Layanan Dan Literasi Keuangan Syariah Terhadap Keputusan Menjadi Nasabah BPR Syariah - Ilyas Lamuda; Sofiwati Sanusi Limpo; Moh. Affan Suyanto; Deby Rita Karundeng (CV. Dalle’ Deceng Abeeayla, 2026)
This study aims to determine the extent to which Promotion, Service Quality, and Islamic Financial Literacy influence the decision to become a customer at BPR Syariah Khairan Inti Amanah. The analysis method used is quantitative with Multiple Linear Regression analysis using IBM SPSS Statistics software version 26. The results of this study indicate that (1) Promotion has a positive and significant indirect effect on the decision to become a customer, (2) Service Quality does not have a significant indirect effect on the decision to become a customer, (3) Islamic Financial Literacy does not have a significant indirect effect on the decision to become a customer. These three variables together cannot influence the decision to become a customer of BPRS, due to other factors such as the type of information media used being more up-to-date with the era of digitalization, and the service quality that needs to be considered is the one that can provide solutions to customers by offering fast, real-time services without coming to the office. Trust is also a factor that can influence, even though the understanding of knowledge in managing finances in an Islamic way increases, it does not necessarily increase the decision to become a customer.